2016
DOI: 10.5812/jjm.29384
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Finger Nuclease: A New Approach to Overcome Beta-Lactam Antibiotic Resistance

Abstract: Background:The evolution of antibiotic-resistant bacteria (ARB) and antibiotic-resistance genes (ARGs) has been accelerated recently by the indiscriminate application of antibiotics. Antibiotic resistance has challenged the success of medical interventions and therefore is considered a hazardous threat to human health.Objectives:The present study aimed to describe the use of zinc finger nuclease (ZFN) technology to target and disrupt a plasmid-encoded β-lactamase, which prevents horizontal gene transfer-mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…For these reasons, among others, it is crucial that we begin to develop new treatments to combat bacterial infection. Researchers have already begun investigating potential new antimicrobial strategies (22), such as the use of antimicrobial peptides (23, 24), phage therapy (25, 26), and gene-editing enzymes (27, 28). Here, we report another promising novel approach: the use of predatory bacteria to control Gram-negative human pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, among others, it is crucial that we begin to develop new treatments to combat bacterial infection. Researchers have already begun investigating potential new antimicrobial strategies (22), such as the use of antimicrobial peptides (23, 24), phage therapy (25, 26), and gene-editing enzymes (27, 28). Here, we report another promising novel approach: the use of predatory bacteria to control Gram-negative human pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has suggested that zinc finger nuclease may be a potential agent to overcome β-lactam antibiotic resistance (23). Antibiotic resistance of Klebsiella pneumoniae has challenged the therapeutic efficacy for patients with pneumonia (35).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study indicates that zinc finger nuclease technology is able to target and disrupt gene-encoded β-lactamase, which prevents horizontal gene transfer-mediated evolution of antibiotic resistant bacteria and antibiotic resistance genes (23). Therefore, we analyzed the function of zinc finger nuclease in Klebsiella pneumoniae.…”
Section: Efficacy Of Zinc Finger Nuclease For Growth Of Klebsiella Pnmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be the possible explanation of severe lung injury in COVID -19 patients. Moreover, TRPM2 ability to response to oxidative stress made it a promising target for development of new small molecule and therapeutic approach suchas aptamer(31) and gene editing tools(32,33)(Fig 1).…”
mentioning
confidence: 99%